PRELIMINARY EVALUATION OF COLOR STABILITY OF DATE FRUIT TABLETS - D. Megdoud; M. S. Galouz; S. Rahal; S. Benamara (Пищевые системы, 2022)
This paper reports on preliminary qualitative evaluation of relationship between color change and water activity (aw) of date (Phoenix dactylifera L., var. Mech-Degla) fruit tablets (DFTs) as natural supplement, in view to optimize their storage conditions. Eight types of DFTs were obtained, according to: i) mean particle size (225 and 282 μm) of the used fruit powder, and ii) compression pressure (5, 10, 15 and 20 kN) applied during the tableting process. The experimental adsorption curves, determined at 25°C using static-gravimetric method, were fitted to GAB (Guggenheim–Anderson–de Boer) and BET (Brunauer–Emmett–Teller) models. Results showed that the DFT color is significantly sensitive to aw since beyond the aw threshold value of 0.44, the DFT color changes from light grey to dark brown, independently of the particle size of fruit powder and compression pressure. Concerning the isotherm modeling, the both models tested seem especially suitable (R≈0,96 0.3≤MRE≤5 and SE≈0.03) for describing the experimental data for DFT obtained under a compression pressure of 5 kN from date fruit powder with mean particle size of 225 μm. The DFT color stability is considerably influenced by the environmental humidity. Considering the importance of color for consumer acceptance, the study deserves to be deepened concerning the quantitative analysis of the color (CIELab system), packaging of the tablets, etc.